2021
DOI: 10.1101/2021.11.30.21266988
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-muscle Invasive Bladder Cancer Molecular Subtypes Predict Differential Response to Intravesical Bacillus Calmette-Guérin

Abstract: SummaryThe recommended treatment for patients with high-risk non-muscle invasive bladder cancer (HR-NMIBC) is tumor resection followed by adjuvant Bacillus Calmette-Guérin (BCG) bladder instillations. However, only 50% of patients benefit from this therapy. In case of progression to advanced disease, patients must undergo a radical cystectomy with significant morbidity and have a poor clinical outcome. Identifying tumors least likely to respond to BCG can translate into alternative treatments, such as early ra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 92 publications
2
9
0
Order By: Relevance
“…Our findings demonstrate a robust association between CD79a+ B cell infiltration in both stromal and epithelial compartments, which is more pronounced in high-grade tumors from female patients who experienced early recurrence and disease progression following BCG therapy. These observations align with current literature highlighting the importance of CD79a+ B cells in driving tumor progression and fostering resistance to BCG therapy, particularly within the stromal milieu [21].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings demonstrate a robust association between CD79a+ B cell infiltration in both stromal and epithelial compartments, which is more pronounced in high-grade tumors from female patients who experienced early recurrence and disease progression following BCG therapy. These observations align with current literature highlighting the importance of CD79a+ B cells in driving tumor progression and fostering resistance to BCG therapy, particularly within the stromal milieu [21].…”
Section: Discussionsupporting
confidence: 90%
“…The patients in this cohort were stratified into different quartiles according to their CD79a and CD163 gene expression levels. Patient clinical demographics and outcome data was extracted from the supplementary information provided by de Jong et al ., [21] These clinical attributes were then combined with the gene expression profiles of the primary tumors. Subsequently, an analysis was conducted using the time to disease progression and the progression status in R version 4.2.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular subtype associated with the worst PFS and recurrence, termed BCG response subtype 3 (BRS3), was found to have overexpression of immunosuppressive genes, including PD-1/PD-L1 and chemokines, as well as overexpression of basal and epithelial-to-mesenchymal transition (EMT) activation markers. PFS in this cohort was 61%, compared to 78% and 83% in the other two molecular subtypes (20). Kim et al similarly identified three molecular subtypes exhibiting distinct prognostic features (21).…”
Section: Molecular Subtypes and Implications For Nmibcmentioning
confidence: 55%
“…2). Three molecular subtypes with a distinct response to Bacillus Calmette-Guérin (BCG) were recently introduced [16]. These subtypes are currently being investigated in a prospective trial assessing their ability to predict response to BCG therapy.…”
Section: Rna Expression In Non-muscle-invasive Bcmentioning
confidence: 99%